Impact of interprofessional geriatric teamwork on students' perceptions of older persons and collaborative practice. Issue 1 (2nd January 2023) - Willis, Jada L.; Hawley, Diane A.; Watson, Jennifer B.; Jackson, D. Lynn; Severance, Jennifer J.; Butler Carroll, Traci; Knebl, Janice A.
ABSTRACT: Health professions programs lack sufficient exposure to geriatric education in curricula. The Seniors Assisting in Geriatric Education (SAGE) Program exposes interprofessional (IP) teams of health professions students to older adults. To determine the impact of an interprofessional geriatric educational experience on student perceptions of team collaboration and older adults. IP teams of three or four students (n = 662) representing eight disciplines from two institutions were paired with an older adult to promote person-centered care over three semesters. Students completed two online questionnaires (pre- and post-SAGE Program, ~10 min). 136 students completed both questionnaires. Three IP collaborative practice sub-competencies under the Roles & Responsibilities and Interprofessional Communication Core Competencies increased significantly from pre- to post-SAGE Program (p ≤ 0.002). Comparison of the means for attitudes toward geriatric patients revealed statistically significant improvement in one item, Compassion ( p < .002). The SAGE Program had a positive impact on IP collaborative practice and attitudes toward older people in some, but not all, areas.